2021
DOI: 10.14710/jitaa.47.1.55-64
|View full text |Cite
|
Sign up to set email alerts
|

Early fattening and improving feeding quality of Kejobong goats could reduce methane production and improve meat production

Abstract: An experimental study was carried out to evaluate the implication of early fattening of Kejobong goats by improving feeding quality on methane production and meat production. Sixteen goats (8 young and 8 mature) were raised for 4 months study period. Nested design was used in this study, with young and mature as a nest factor, and diet (G7C3: 70% grass and 30% concentrate and G3C7: 30% grass and 70% concentrate) as the treatments. The main parameters observed were DMI, BWG, carcass (CWG) and meat weight gain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A study by Restitrisnani et al (2022) revealed that the body weight of Kejobong goats fed 30% grass and 70% concentrate increased by 94.95 g/d, which was greater (P<0.01) than that of those fed 70% grass and 30% concentrate (58.70 g). Panjono et al (2014) Growth is an important physiological activity in livestock that produce meat.…”
Section: Introductionmentioning
confidence: 94%
“…A study by Restitrisnani et al (2022) revealed that the body weight of Kejobong goats fed 30% grass and 70% concentrate increased by 94.95 g/d, which was greater (P<0.01) than that of those fed 70% grass and 30% concentrate (58.70 g). Panjono et al (2014) Growth is an important physiological activity in livestock that produce meat.…”
Section: Introductionmentioning
confidence: 94%